Completely biodegradable resin as well as preparation method and application thereof
By blending modified carbon dioxide-based polycarbonate materials with toughening agents and antiblocking agents, a completely biodegradable resin with high elongation of break and tensile strength was prepared, which solved the material brittleness and processing problems, achieved efficient gas barrier and antibacterial properties, and was suitable for plastic film applications.
Patent Information
- Application Number
- CN202510528032.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-07-29
- Estimated Expiration
- 2045-04-25
AI Technical Summary
The existing carbon dioxide-based polycarbonate materials such as PPC-X, PPC-P, and PPC-Plus have increased molecular structure rigidity, resulting in high brittleness and poor impact resistance, making it difficult to process into film products. At the same time, their production relies on non-renewable petroleum resources, which is not in line with the concept of sustainable development.
By blending and modifying carbon dioxide-based polycarbonate with toughening agents, anti-adhesive agents and additives, completely biodegradable resins, including toughening agents such as polyethylene oxide, polypropylene oxide, polycarbonate-co-polyurethane copolymers, anti-adhesive agents such as paraffin and stearic acid soap, fatty acids and their salts, etc., to improve the toughness and processing performance of the material, and apply anti-bacterial liquid to the surface of the film to enhance anti-bacterial function.
It significantly improves the elongation and tensile strength of the material, meets the needs of film processing, and has good gas barrier properties and long-lasting antibacterial functions. It is suitable for plastic wrap, food packaging film and agricultural mulching film.
Smart Images

Figure CN120383814A_ABST
Abstract
Description
Technical Field
[0001] At present, plastic products have been widely used in many fields due to their advantages such as light weight, high strength, stable chemical properties and low cost. However, traditional plastic products are difficult to naturally degrade in the environment, posing great challenges to social sustainable development and environmental governance. Biodegradable resins have started to emerge in the fields of agricultural films, packaging films, disposable products, etc. in China. At present, resins such as PLA, PBAT, and PBS are the most widely used biodegradable resins. However, the main raw materials of PLA among these biodegradable resins are food crops rich in starch or sugars such as corn and sugarcane. The sugars in plants are converted into lactic acid through a fermentation process and then polymerized to form PLA resin. Large-scale production of PLA may occupy arable land resources and easily lead to problems such as "competing with people for food and competing with food for land". The synthesis of PBAT and PBS relies on non-renewable petroleum resources, which does not conform to the concept of sustainable development.
[0002] Carbon dioxide-based polycarbonates are environmentally friendly polymer materials synthesized mainly from carbon dioxide, with biodegradability and low-carbon emission characteristics, and are regarded as an important direction to replace traditional petroleum-based plastics. At present, several new members have been added to the family of carbon dioxide-based polycarbonates, such as PPC-X, PPC-P, PPC-Plus, etc. Structures such as benzene rings and cyclohexanes are introduced into the molecular structures of these materials, increasing the rigidity of their molecular chains and raising the glass transition temperature from the initial 32 °C of poly(ethylene carbonate) (PPC) to about 50 °C. Therefore, materials such as PPC-X, PPC-P, and PPC-Plus can meet basic usage requirements. And the mass fraction of carbon dioxide in the molecular structures of these materials is about 43%, which can reduce greenhouse gas emissions and the dependence on petroleum resources, and can also be naturally degraded in the environment after being used and discarded. However, the increased rigidity of the molecular structures of materials such as PPC-X, PPC-P, and PPC-Plus results in greater brittleness of the materials and poor impact resistance, making it difficult to be smoothly processed into film products.
[0003] For example, Zhang Tianwei from the research group of Professor Meng Yuezhong at Sun Yat-sen University mentioned that the elongation at break of PPC-P is only 6%, showing brittleness. He improved the mechanical elongation at break and toughness of PPC-P by blending and modifying PPC-P with the commercial biodegradable plastic PBAT, but at the same time significantly reduced the gas barrier performance of PPC-P (Zhang Tianwei, Liang Jiaxin, Yue Shuangshuang, et al. Acta Polymerica Sinica, 2023, 54(8): 1144-1154.).
[0004] In addition, when Deng Jiangtao developed a high-barrier film, he also mentioned that the elongation of PPC-P was only 6%, indicating brittleness (High-Gas-Barrier and Biodegradable PPC-P / PBAT Composite Films Coated by Poly(vinyl alcohol) / borax Complexes. Surfaces 2024, 7, 517–528.). He prepared a high-barrier plastic film by blending and modifying PPC-P with commercial biodegradable plastic PBAT to produce a plastic film, and then coating the surface with a layer of polyvinyl alcohol and boron compound blend to enhance other barrier capabilities.
[0005] Fan Congxiao synthesized and prepared three PPC-P polymers with different sequence structures, and the final test results also proved that PPC-P materials are hard and brittle materials (Fan Congxiao, Liang Jiaxin, Ye Shuxian, et al. Controllable synthesis and performance study of carbon dioxide / propylene oxide / phthalic anhydride terpolymers with different sequence structures, Acta Polymerica Sinica, 2022, 53(5):497-504.).
[0006] There are relatively more reports on PPC-P, while there are relatively few reports on PPC-X and PPC-Plus, because these three types of resins are still in the industrialization and market stage. However, PPCX and PPC-Plus also have six-membered ring structural units of benzene rings or cyclohexane in their molecular structures, which will increase the rigidity of the final synthesized materials and reduce elongation or toughness. They are both hard and brittle materials and must be toughened to improve their practicality and application range.
[0007] Therefore, the present invention aims to enhance the elongation and toughness of materials such as PPC-X, PPC-P, and PPC-Plus through modification technology, improve their molding and processing performance, and at the same time impart antibacterial function to their surfaces, thereby hoping to promote their application in the field of plastic films. Summary of the Invention
[0008] In view of this, the present invention provides a fully biodegradable resin comprising the following raw materials:
[0009] Carbon dioxide-based polycarbonate, toughening agent, anti-adhesion agent, additives;
[0010] The carbon dioxide-based polycarbonate includes any one or a blend of two or more of poly(propylene carbonate-co-propylene phthalate) copolymer, abbreviated as PPC-P, poly(propylene carbonate-co-cyclohexene oxide-phthalate) copolymer, abbreviated as PPC-X, or a copolymer prepared by catalytic polymerization of four or more monomers such as carbon dioxide, propylene oxide, phthalic anhydride, cyclohexene oxide, and other compounds, abbreviated as PPC-Plus.
[0011] Further, when the carbon dioxide-based polycarbonate is PPC-X, the mass ratio of the carbon dioxide-based polycarbonate, toughening agent, anti-blocking agent, and additive is 100:(20 - 25):(1 - 5):(0.1 - 2); when the carbon dioxide-based polycarbonate is PPC-P, the mass ratio of the carbon dioxide-based polycarbonate, toughening agent, anti-blocking agent, and additive is 100:(5 - 50):(1 - 5):(0.1 - 2).
[0012] Further, the toughening agent includes any one or a mixture of two or more of polyethylene oxide (PEO), polypropylene oxide (PPO), polycarbonate-co-polyurethane copolymer (PPC-TPU), poly(methyl ethylene carbonate) (PPC), and aliphatic polycarbonate diol (PCDL).
[0013] Further, the anti-blocking agent includes any one or a mixture of two or more of paraffin, stearic acid soaps (calcium, magnesium, zinc), fatty acid amides, polydimethylsiloxane, and talcum powder.
[0014] Further, the additive includes fatty acids and their salts. Preferably, the additive includes stearic acid and its salts.
[0015] The present invention also provides a preparation method of the completely biodegradable resin, which includes mixing the raw materials in proportion, drying, extruding by screw melt blending, cooling, and pelletizing to obtain the modified completely biodegradable resin.
[0016] Further, the drying temperature is 50°C to 70°C, and the drying time is 8 to 10 h.
[0017] Further, the temperature range of the screw melt blending is 120°C to 170°C.
[0018] An application of a completely biodegradable resin is to prepare a plastic film from the completely biodegradable resin, and the thickness range of the plastic film is 5 μm to 200 μm.
[0019] Further, the method for preparing the plastic film includes, but is not limited to, blow molding, casting, calendering, and solution casting molding processes.
[0020] Further, an antibacterial solution is coated on both sides of the plastic film. The composition of the antibacterial solution includes 0.5% - 5% of an antibacterial agent, 0.5% - 2% of a silane coupling agent, and 93% - 99% of absolute ethanol. The thickness of the antibacterial solution coating is 0.5 μm - 20 μm.
[0021] Further, the antibacterial solution is prepared by measuring according to the above proportions and stirring and dispersing evenly at room temperature until the solution is clear and transparent.
[0022] Further, the preparation method of the antibacterial agent refers to the invention patent with the application number 202311154338.8, titled "A Ternary Copolymer Quaternary Ammonium Salt Polymer Antibacterial Agent and Its Preparation Method and Application".
[0023] Further, the silane coupling agent includes any one of KH-550, KH-560, KH-570, A151, A171, etc.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The modified completely biodegradable resin of the present invention not only has good tensile strength compared with the unmodified PPC-P, PPC-X or PPC-Plus, but also significantly improves the elongation at break of the material, and can meet the requirements of processing technologies such as blown film and practical applications.
[0026] The modified completely biodegradable resin of the present invention is completely biodegradable compared with traditional resins such as polyethylene, polypropylene, polyester, polyvinyl chloride, ethylene-vinyl acetate copolymer, etc., and the degradation period can be regulated.
[0027] The plastic film prepared by the present invention has higher gas barrier properties for gases such as carbon dioxide, oxygen and water vapor compared with traditional films such as polyethylene, polypropylene, polyester, polyvinyl chloride, ethylene-vinyl acetate copolymer, etc., or biodegradable plastic films such as PBAT, PLA, PBS, etc., and also has a long-lasting antibacterial function, and is very suitable for plastic film application fields such as food wrap, food packaging film, agricultural film, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a comparative chart of the mechanical property changes of the materials in Examples 1-2 and Comparative Examples 1-4.
[0029] Figure 2 It is a comparative chart of the mechanical property changes of the materials in Examples 3-6 and Comparative Example 5.
[0030] Figure 3 It is a test chart of the antibacterial property of the material in Example 1. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0031] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of them. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts belong to the scope protected by the present invention.
[0032] In the following embodiments, the test methods or testing methods, unless otherwise specified, are all conventional methods; the raw materials and auxiliaries, unless otherwise specified, are all obtained from conventional commercial channels or prepared by conventional methods.
[0033] PPC-X (Beijing Xuyang Technology Co., Ltd., grade: PPCX-103), PPC-P (Shandong Lianxin Environmental Protection Technology Co., Ltd., grade: PPC-P LX101), PPC-TPU (Jiangsu Zhongke Jinlong New Environmental Protection Materials Co., Ltd., grade: PPC-TPUT1), PEO-10W (Dow Chemical, USA, grade: POLYOX WSR N10), oleic acid amide (PMC Group, USA, grade: Armoslip CP), polydimethylsiloxane (Hubei Chengfeng Chemical Co., Ltd., grade: PDMS), stearic acid (IOI Group Co., Ltd., Malaysia, grade: SA-1801).
[0034] Example 1
[0035] A preparation method of a completely biodegradable resin, the specific steps are as follows: Weigh the following raw materials in proportion, 500 g of PPC-X, 100 g of PPC-TPU, 5.0 g of oleic acid amide, and 2.5 g of stearic acid. Then premix the components, and then dry them at 50 °C for 10 h. Finally, set the temperatures of each zone in the screw mixing equipment as follows: zone 1 is 50 °C (feed inlet), zone 2 is 120 °C, zone 3 is 160 °C, zone 4 is 165 °C, zone 5 is 170 °C, zone 6 is 160 °C (die). The feeding speed is 15 revolutions per minute, the screw speed is 100 revolutions per minute, and the granulator speed is 20 revolutions per minute. Under these process conditions, carry out melt blending, extrusion, cooling, and granulation to obtain the modified completely biodegradable resin.
[0036] The steps of a method for preparing a film of a completely biodegradable modified resin are as follows:
[0037] Put the modified completely biodegradable resin into the screw hopper, then melt it in the temperature range of 150°C to 160°C, extrude it from the die and enter a three-roll calender (the front roll is at 150°C and the rotation speed is 50 revolutions per minute, the middle roll is at 160°C and the rotation speed is 60 revolutions per minute, the rear roll is at 150°C and the rotation speed is 55 revolutions per minute). Set the inter-roll pressure to 10 MPa, the roll gap to 30 μm to 50 μm, and the cooling air temperature to 30°C. After cooling and forming, carry out double-sided coating of the antibacterial liquid coating through a coater (control the coating thickness to be 0.5 μm to 3 μm), and finally dry at 35°C, wind up, and package.
[0038] The preparation method of the antibacterial liquid is to stir and disperse 0.5% to 5% of the antibacterial agent, 0.5% to 2% of the silane coupling agent, and 93% to 99% of absolute ethanol evenly at room temperature to obtain the antibacterial liquid.
[0039] Example 2
[0040] A preparation method of a completely biodegradable resin, the specific steps are as follows: Weigh the following raw materials in proportion, 500 g of PPC-X, 125 g of PPC-TPU, 5.0 g of oleic acid amide, and 2.5 g of stearic acid. Then premix each component, and then dry it at 50°C for 10 h. Finally, set the temperatures of each zone in the screw mixing equipment as follows: the first zone is 50°C (feed inlet), the second zone is 120°C, the third zone is 160°C, the fourth zone is 165°C, the fifth zone is 170°C, and the sixth zone is 160°C (die). The feeding speed is 15 revolutions per minute, the screw rotation speed is 100 revolutions per minute, and the granulator rotation speed is 20 revolutions per minute. Under these process conditions, carry out melt blending, extrusion, cooling, and granulation to obtain the modified completely biodegradable resin.
[0041] The steps of a method for preparing a film of a completely biodegradable modified resin are as follows:
[0042] Put the modified completely biodegradable resin into the screw hopper, then melt it in the temperature range of 150°C to 160°C, extrude it from the die and enter a three-roll calender (the front roll is at 150°C and the rotation speed is 50 revolutions per minute, the middle roll is at 160°C and the rotation speed is 60 revolutions per minute, the rear roll is at 150°C and the rotation speed is 55 revolutions per minute). Set the inter-roll pressure to 10 MPa, the roll gap to 30 μm to 50 μm, and the cooling air temperature to 30°C. After cooling and forming, carry out double-sided coating of the antibacterial liquid coating through a coater (control the coating thickness to be 0.5 μm to 3 μm), and finally dry at 35°C, wind up, and package.
[0043] The preparation method of the antibacterial liquid is to stir and disperse 0.5% to 5% of the antibacterial agent, 0.5% to 2% of the silane coupling agent, and 93% to 99% of absolute ethanol evenly at room temperature to obtain the antibacterial liquid.
[0044] Comparative Example 1
[0045] A preparation method of a completely biodegradable resin, the specific steps are as follows: Weigh the following raw materials proportionally: 500 g of PPC-X500, 50 g of PPC-TPU, 5.0 g of oleic acid amide, and 2.5 g of stearic acid. Then premix each component, and then dry at 50 °C for 10 h. Finally, set the temperatures of each zone in the screw mixing equipment as follows: Zone 1: 50 °C (feed inlet), Zone 2: 120 °C, Zone 3: 160 °C, Zone 4: 165 °C, Zone 5: 170 °C, Zone 6: 160 °C (die). The feeding speed is 15 revolutions per minute, the screw rotation speed is 100 revolutions per minute, and the granulator rotation speed is 20 revolutions per minute. Under these process conditions, carry out melt blending, extrusion, cooling, and granulation to obtain the modified completely biodegradable resin.
[0046] The steps of a method for preparing a film of a completely biodegradable modified resin are as follows:
[0047] Put the modified completely biodegradable resin into the screw hopper, then melt it in the temperature range of 150 °C to 160 °C, extrude it from the die and enter a three-roll calender (the front roll is 150 °C, the rotation speed is 50 revolutions per minute, the middle roll is 160 °C, the rotation speed is 60 revolutions per minute, the rear roll is 150 °C, the rotation speed is 55 revolutions per minute). Set the roll pressure to 10 MPa, the roll gap to 30 μm to 50 μm, and the cooling air temperature to 30 °C. After cooling and forming, carry out double-sided coating of the antibacterial liquid coating through a coater (control the coating thickness to be 0.5 μm to 3 μm). Finally, dry at 35 °C, wind up, and package.
[0048] The preparation method of the antibacterial liquid is to stir and disperse 0.5% to 5% of the antibacterial agent, 0.5% to 2% of the silane coupling agent, and 93% to 99% of absolute ethanol evenly at room temperature to obtain the antibacterial liquid.
[0049] Comparative Example 2
[0050] A preparation method of a completely biodegradable resin, the specific steps are as follows: Weigh the following raw materials proportionally: 500 g of PPC-X500, 75 g of PPC-TPU, 5.0 g of oleic acid amide, and 2.5 g of stearic acid. Then premix each component, and then dry at 50 °C for 10 h. Finally, set the temperatures of each zone in the screw mixing equipment as follows: Zone 1: 50 °C (feed inlet), Zone 2: 120 °C, Zone 3: 160 °C, Zone 4: 165 °C, Zone 5: 170 °C, Zone 6: 160 °C (die). The feeding speed is 15 revolutions per minute, the screw rotation speed is 100 revolutions per minute, and the granulator rotation speed is 20 revolutions per minute. Under these process conditions, carry out melt blending, extrusion, cooling, and granulation to obtain the modified completely biodegradable resin.
[0051] The steps of a method for preparing a film of a completely biodegradable modified resin are as follows:
[0052] Put the modified completely biodegradable resin into the screw hopper, then melt it in the temperature range of 150°C to 160°C, extrude it from the die and enter a three-roll calender (the front roll is at 150°C and the rotation speed is 50 revolutions per minute, the middle roll is at 160°C and the rotation speed is 60 revolutions per minute, the rear roll is at 150°C and the rotation speed is 55 revolutions per minute). Set the inter-roll pressure to 10 MPa, the roll gap to 30 μm to 50 μm, and the cooling air temperature to 30°C. After cooling and forming, carry out double-sided coating with an antibacterial liquid coating (control the coating thickness to be 0.5 μm to 3 μm), and finally dry at 35°C, wind up, and package.
[0053] The preparation method of the antibacterial liquid is to stir and disperse 0.5% to 5% of antibacterial agent, 0.5% to 2% of silane coupling agent, and 93% to 99% of absolute ethanol evenly at room temperature to obtain the antibacterial liquid.
[0054] Comparative Example 3
[0055] A preparation method of a completely biodegradable resin, the specific steps are as follows: Weigh the following raw materials in proportion, 500 g of PPC-X, 150 g of PPC-TPU, 5.0 g of oleic acid amide, and 2.5 g of stearic acid. Then premix each component, and then dry it at 50°C for 10 h. Finally, set the temperatures of each zone in the screw mixing equipment as follows: Zone 1 is 50°C (feed inlet), Zone 2 is 120°C, Zone 3 is 160°C, Zone 4 is 165°C, Zone 5 is 170°C, Zone 6 is 160°C (die). The feeding speed is 15 revolutions per minute, the screw rotation speed is 100 revolutions per minute, and the granulator rotation speed is 20 revolutions per minute. Under these process conditions, carry out melt blending, extrusion, cooling, and granulation to obtain the modified completely biodegradable resin.
[0056] The steps of a method for preparing a film of a completely biodegradable modified resin are as follows:
[0057] Put the modified completely biodegradable resin into the screw hopper, then melt it in the temperature range of 150°C to 160°C, extrude it from the die and enter a three-roll calender (the front roll is at 150°C and the rotation speed is 50 revolutions per minute, the middle roll is at 160°C and the rotation speed is 60 revolutions per minute, the rear roll is at 150°C and the rotation speed is 55 revolutions per minute). Set the inter-roll pressure to 10 MPa, the roll gap to 30 μm to 50 μm, and the cooling air temperature to 30°C. After cooling and forming, carry out double-sided coating with an antibacterial liquid coating (control the coating thickness to be 0.5 μm to 3 μm), and finally dry at 35°C, wind up, and package.
[0058] The preparation method of the antibacterial liquid is to stir and disperse 0.5% to 5% of antibacterial agent, 0.5% to 2% of silane coupling agent, and 93% to 99% of absolute ethanol evenly at room temperature to obtain the antibacterial liquid.
[0059] Comparative Example 4
[0060] The difference from Example 1 is that it does not contain a toughening agent.
[0061] Example 3
[0062] A preparation method of a completely biodegradable resin, the specific steps are as follows: Weigh the following raw materials in proportion, 500 g of PPC-P5, 25 g of PEO-10W (PEO with a molecular weight of 100,000), 5.0 g of polydimethylsiloxane, and 2.5 g of stearic acid. Then premix the components, and then dry them at 50 °C for 10 h. Finally, set the temperatures of each zone in the screw mixing equipment as follows: Zone 1 is 50 °C (feed inlet), Zone 2 is 120 °C, Zone 3 is 140 °C, Zone 4 is 150 °C, Zone 5 is 150 °C, and Zone 6 is 140 °C (die). The feeding speed is 15 revolutions per minute, the screw rotation speed is 100 revolutions per minute, and the granulator rotation speed is 20 revolutions per minute. Under these process conditions, carry out melt blending, extrusion, cooling, and granulation to obtain the modified completely biodegradable resin.
[0063] The steps of a method for preparing a film of a completely biodegradable modified resin are as follows:
[0064] Put the modified completely biodegradable resin into the screw hopper, then melt it in the temperature range of 150 °C to 160 °C, extrude it from the die and enter a three-roll calender (the front roll is 150 °C and the rotation speed is 50 revolutions per minute, the middle roll is 160 °C and the rotation speed is 60 revolutions per minute, the rear roll is 150 °C and the rotation speed is 55 revolutions per minute). Set the roll pressure to 10 MPa and the roll spacing to 30 μm to 50 μm. The cooling air temperature is 30 °C. After cooling and forming, carry out double-sided coating of an antibacterial liquid coating (control the coating thickness to be 0.5 μm to 3 μm) through a coater, and finally dry at 35 °C, wind up, and package.
[0065] The preparation method of the antibacterial liquid is to stir and disperse 0.5% to 5% of an antibacterial agent, 0.5% to 2% of a silane coupling agent, and 93% to 99% of absolute ethanol evenly at room temperature to obtain the antibacterial liquid.
[0066] Example 4
[0067] A preparation method of a completely biodegradable resin, the specific steps are as follows: Weigh the following raw materials in proportion, 500 g of PPC-P500, 40 g of PEO-10W (PEO with a molecular weight of 100,000), 5.0 g of polydimethylsiloxane, and 2.5 g of stearic acid. Then premix each component, and then dry at 50 °C for 10 h. Finally, set the temperatures of each zone in the screw mixing equipment as follows: Zone 1: 50 °C (feed inlet), Zone 2: 120 °C, Zone 3: 140 °C, Zone 4: 150 °C, Zone 5: 150 °C, Zone 6: 140 °C (die). The feeding speed is 15 revolutions per minute, the screw speed is 100 revolutions per minute, and the granulator speed is 20 revolutions per minute. Under these process conditions, carry out melt blending, extrusion, cooling, and granulation to obtain the modified completely biodegradable resin.
[0068] The steps of a method for preparing a film of a completely biodegradable modified resin are as follows:
[0069] Put the modified completely biodegradable resin into the screw hopper, then melt it in the temperature range of 150 °C to 160 °C, and after extruding from the die, enter a three-roll calender (front roll: 150 °C, speed: 50 revolutions per minute, middle roll: 160 °C, speed: 60 revolutions per minute, rear roll: 150 °C, speed: 55 revolutions per minute). Set the roll pressure to 10 MPa and the roll spacing to 30 μm to 50 μm. The cooling air temperature is 30 °C. After cooling and forming, carry out double-sided coating of an antibacterial liquid coating through a coater (control the coating thickness to be 0.5 μm to 3 μm), and finally dry at 35 °C, wind up, and package.
[0070] The preparation method of the antibacterial liquid is to stir and disperse 0.5% to 5% of an antibacterial agent, 0.5% to 2% of a silane coupling agent, and 93% to 99% of absolute ethanol evenly at room temperature to obtain the antibacterial liquid.
[0071] Example 5
[0072] A preparation method of a completely biodegradable resin, the specific steps are as follows: Weigh the following raw materials in proportion, 500 g of PPC-P500, 60 g of PEO-10W (PEO with a molecular weight of 100,000), 5.0 g of polydimethylsiloxane, and 2.5 g of stearic acid. Then premix each component, and then dry at 50 °C for 10 h. Finally, set the temperatures of each zone in the screw mixing equipment as follows: Zone 1: 50 °C (feed inlet), Zone 2: 120 °C, Zone 3: 140 °C, Zone 4: 150 °C, Zone 5: 150 °C, Zone 6: 140 °C (die). The feeding speed is 15 revolutions per minute, the screw speed is 100 revolutions per minute, and the granulator speed is 20 revolutions per minute. Under these process conditions, carry out melt blending, extrusion, cooling, and granulation to obtain the modified completely biodegradable resin.
[0073] The steps of a method for preparing a film of a completely biodegradable modified resin are as follows:
[0074] Put the modified completely biodegradable resin into the screw hopper, then melt it in the temperature range of 150°C to 160°C, extrude it from the die and enter a three-roll calender (the front roll is at 150°C and the rotation speed is 50 revolutions per minute, the middle roll is at 160°C and the rotation speed is 60 revolutions per minute, the rear roll is at 150°C and the rotation speed is 55 revolutions per minute). Set the pressure between the rolls to 10 MPa, the roll spacing to 30 μm to 50 μm, and the cooling air temperature to 30°C. After cooling and forming, carry out double-sided coating of the antibacterial liquid coating through a coater (control the coating thickness to be 0.5 μm to 3 μm), and finally dry at 35°C, wind up, and package.
[0075] The preparation method of the antibacterial liquid is to stir and disperse 0.5% to 5% of the antibacterial agent, 0.5% to 2% of the silane coupling agent, and 93% to 99% of absolute ethanol evenly at room temperature to obtain the antibacterial liquid.
[0076] Example 6
[0077] A preparation method of a completely biodegradable resin, the specific steps are as follows: Weigh the following raw materials in proportion, 500 g of PPC-P, 75 g of PEO-10W (PEO with a molecular weight of 100,000), 5.0 g of polydimethylsiloxane, and 2.5 g of stearic acid. Then premix each component, and then dry it at 50°C for 10 h. Finally, set the temperatures of each zone in the screw mixing equipment as follows: the first zone is 50°C (feed inlet), the second zone is 120°C, the third zone is 140°C, the fourth zone is 150°C, the fifth zone is 150°C, and the sixth zone is 140°C (die). The feeding speed is 15 revolutions per minute, the screw rotation speed is 100 revolutions per minute, and the granulator rotation speed is 20 revolutions per minute. Under these process conditions, carry out melt blending, extrusion, cooling, and granulation to obtain the modified completely biodegradable resin.
[0078] The steps of a method for preparing a film of a completely biodegradable modified resin are as follows:
[0079] Put the modified completely biodegradable resin into the screw hopper, then melt it in the temperature range of 150°C to 160°C, extrude it from the die and enter a three-roll calender (the front roll is at 150°C and the rotation speed is 50 revolutions per minute, the middle roll is at 160°C and the rotation speed is 60 revolutions per minute, the rear roll is at 150°C and the rotation speed is 55 revolutions per minute). Set the pressure between the rolls to 10 MPa, the roll spacing to 30 μm to 50 μm, and the cooling air temperature to 30°C. After cooling and forming, carry out double-sided coating of the antibacterial liquid coating through a coater (control the coating thickness to be 0.5 μm to 3 μm), and finally dry at 35°C, wind up, and package.
[0080] The preparation method of the antibacterial liquid is to stir and disperse 0.5% to 5% of the antibacterial agent, 0.5% to 2% of the silane coupling agent, and 93% to 99% of absolute ethanol evenly at room temperature to obtain the antibacterial liquid.
[0081] Comparative Example 5
[0082] The difference from Example 3 is that the PEO-10W toughening agent was not added.
[0083] Example 7
[0084] A preparation method of a completely biodegradable resin, the specific steps are as follows: Weigh the following raw materials in proportion, 500 g of PPC-X, 40 g of PEO-10W, 5.0 g of oleic acid amide, and 2.5 g of stearic acid. Then premix each component, and then dry at 50 °C for 10 h. Finally, set the temperatures of each zone in the screw mixing equipment as follows: Zone 1 is 50 °C (feed inlet), Zone 2 is 120 °C, Zone 3 is 160 °C, Zone 4 is 165 °C, Zone 5 is 170 °C, Zone 6 is 160 °C (die). The feeding speed is 15 revolutions per minute, the screw speed is 100 revolutions per minute, and the granulator speed is 20 revolutions per minute. Under these process conditions, carry out melt blending, extrusion, cooling, and granulation to obtain the modified completely biodegradable resin.
[0085] The steps of a method for preparing a film of a completely biodegradable modified resin are as follows:
[0086] Put the modified completely biodegradable resin into the screw hopper, then melt it in the temperature range of 150 °C to 160 °C, extrude it from the die and enter a three-roll calender (front roll at 150 °C, speed 50 revolutions per minute, middle roll at 160 °C, speed 60 revolutions per minute, rear roll at 150 °C, speed 55 revolutions per minute). Set the roll pressure to 10 MPa and the roll gap to 30 μm to 50 μm. The cooling air temperature is 30 °C. After cooling and forming, carry out double-sided coating of the antibacterial liquid coating through a coater (control the coating thickness to be 0.5 μm to 3 μm). Finally, dry at 35 °C, wind up, and package.
[0087] The preparation method of the antibacterial liquid is to stir and disperse 0.5% to 5% of the antibacterial agent, 0.5% to 2% of the silane coupling agent, and 93% to 99% of anhydrous ethanol evenly at room temperature to obtain the antibacterial liquid.
[0088] Example 8
[0089] A preparation method of a completely biodegradable resin, the specific steps are as follows: Weigh the following raw materials in proportion, 500 g of PPC-P500, 100 g of PPC-TPU, 5.0 g of polydimethylsiloxane, and 2.5 g of stearic acid. Then premix each component, and then dry it at 50 °C for 10 h. Finally, set the temperatures of each zone in the screw mixing equipment as follows: the first zone is 50 °C (feed inlet), the second zone is 120 °C, the third zone is 140 °C, the fourth zone is 150 °C, the fifth zone is 160 °C, and the sixth zone is 150 °C (die). The feeding speed is 15 revolutions per minute, the screw speed is 100 revolutions per minute, and the granulator speed is 20 revolutions per minute. Under these process conditions, carry out melt blending, extrusion, cooling, and granulation to obtain the modified completely biodegradable resin.
[0090] The steps of a method for preparing a film of a completely biodegradable modified resin are as follows:
[0091] Put the modified completely biodegradable resin into the screw hopper, then melt it in the temperature range of 150 °C to 160 °C, and after extruding from the die, enter a three-roll calender (the front roll is 150 °C, the speed is 50 revolutions per minute, the middle roll is 160 °C, the speed is 60 revolutions per minute, and the rear roll is 150 °C, the speed is 55 revolutions per minute). Set the roll gap pressure to 10 MPa and the roll gap to 30 μm to 50 μm, and the cooling air temperature to 30 °C. After cooling and forming, carry out double-sided coating of the antibacterial liquid coating through a coater (control the coating thickness to be 0.5 μm to 3 μm), and finally dry at 35 °C, wind up, and package.
[0092] The preparation method of the antibacterial liquid is to stir and disperse 0.5% to 5% of the antibacterial agent, 0.5% to 2% of the silane coupling agent, and 93% to 99% of anhydrous ethanol evenly at room temperature to obtain the antibacterial liquid.
[0093] Performance test:
[0094] I) Conduct mechanical property tests on Examples 1-8 and Comparative Examples 1-5. The test method:
[0095] Refer to GB / T 1040.3-2006 Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets.
[0096] Test steps: First, under the conditions of 150 °C and 10 MPa, press the modified completely biodegradable resin into a film sample with a thickness of about 200 μm in a flat vulcanizing machine. Then cut it into dumbbell-shaped tensile specimens using a standard cutting die. Then carry out conditioning for 24 h under standard conditions (relative humidity 50%, 25 °C). Then set the tensile speed of the universal mechanical testing machine to 50 mm / min, input parameters such as the average thickness of the specimen and the width of the specimen between the gauge marks, and then carry out the tensile test of the specimen. Each specimen is tested in parallel 5 times, and finally calculate the average value of the mechanical property test of each specimen.
[0097] Refer to GB / T 1043.1-2008 Plastics - Determination of Charpy impact properties - Part 1: Non-instrumented impact test
[0098] Test procedure: First, use an injection molding machine to mold non-notched test specimens with dimensions of 80 mm × 10 mm × 4 mm, and perform conditioning under standard conditions for 24 h. Turn on the Charpy impact tester, wait for 10 minutes to reach equilibrium, then input the test parameters (pendulum weight, specimen information, etc.), and start testing the blank value (the impact energy of the pendulum consumed by air friction resistance). Subsequently, lift the pendulum to the specified height, place the specimen on the supports of the testing machine, align the pendulum cutting edge with the center of the specimen's dimension, and finally release the pendulum. Record the impact energy value displayed by the instrument to complete the impact test. Each specimen is measured in parallel 5 times, and finally calculate the average value of the impact absorption energy of each specimen.
[0099] The results of the mechanical property tests for Examples 1-8 and Comparative Examples 1-5 are shown in Table 1 as follows:
[0100] Table 1
[0101]
[0102] As can be seen from Table 1, the elongation at break and impact strength of the fully biodegradable resin provided by the present invention are significantly improved. The elongation at break of PPC-X without toughener modification is only 3.49%, and the impact strength is 5.7 kJ / m 2 , while after modification by the method provided by the present invention, the elongation at break of PPC-X reaches 99.22%, and the impact strength reaches 36.7 kJ / m 2 .
[0103] And it can be seen from Examples 1-2 and Comparative Examples 1-3 that when the addition amount of the toughener is small, although the tensile strength of PPC-X is improved to some extent, the elongation at break is poor, indicating that the brittleness of PPC-X is still relatively large. When the addition amount of the toughener is large, although the elongation at break of PPC-X is significantly improved, the tensile strength decreases significantly, which cannot meet the requirements of practical applications in film processing. That is, only a specific proportion of the addition amount of the toughener can effectively improve the elongation at break of PPC-X and ensure good tensile strength.
[0104] It can be seen from Examples 3-6 and Comparative Example 5 that compared with unmodified PPC-P, the elongation at break and impact strength of PPC-P modified with a toughener increase several times. Before modification, the elongation of PPC-P is only 3.77%, and the impact strength is only 10.2 kJ / m 2 , and after modification, the elongation of PPC-P is increased to 712.59%, and the impact strength reaches 74.6 kJ / m 2, so that the comprehensive mechanical properties of PPC-P can meet the requirements of processing technologies such as blown film and practical applications.
[0105] As can be seen from Table 1, before modification, PPC-X and PPC-P had high strength, but very low elongation at break and impact strength, with relatively high brittleness and were prone to cracking during film formation. However, after modification with a toughening agent, the elongation at break and toughness of the material were significantly improved, and at the same time, the tensile strength of the material could still meet the requirements of processing technologies such as blown film and practical applications.
[0106] Moreover, since the added toughening agents are all completely biodegradable materials, the biodegradability of the raw materials after modification will not be affected.
[0107] II) Perform barrier property tests on Examples 1-8 and Comparative Examples 1-5. Test method: Refer to GB / T1038.1-2022 Plastics - Films and sheets - Determination of gas permeability - Part 1: Differential pressure method.
[0108] Test steps: First, at 150 °C and 10 MPa, press the modified completely biodegradable resin into a film sample with a thickness of about 200 μm in a flat vulcanizing machine. Then, perform conditioning for 24 h under standard conditions (relative humidity 50%, 25 °C). Next, cut it into test samples of 3.5 cm × 3.5 cm using a standard cutting die. Turn on the power of the gas permeation tester, adjust the flow rates of the corresponding test gas and nitrogen, and wait for 20 minutes for preheating. Paste and seal the 3.5 cm × 3.5 cm test sample in the center of a 3 cm × 3 cm cavity of the tin foil, leaving only 9 cm 2 of the sample area for testing. Subsequently, apply sealing grease to the two sealing surfaces of the test sealing chamber, then stick the tin foil with the film sample in the middle of the test chamber, and finally seal and combine the upper and lower parts of the test chamber and install it at the test chamber position of the gas permeation tester. Set the test parameters: temperature, humidity, gas flow rate, film thickness, film area, etc., and finally select to start the test.
[0109] The test results of the barrier properties of Examples 1-8 and Comparative Examples 1-5, PBAT film, PBS film, PLA film, LDPE film, and PET film are shown in Table 2:
[0110] Table 2
[0111]
[0112]
[0113] As can be seen from Table 2, after the PPC-TPU toughening and modification of PPCX, the gas barrier properties of the material against gases such as carbon dioxide, oxygen, and water vapor have a slight improvement compared to pure PPCX. This may be due to the good compatibility between the two and the physical cross-linking effect between them.
[0114] After the toughening and modification of PPC-P with PEO-10W, the gas barrier properties of the material against gases such as carbon dioxide, oxygen, and water vapor also improve compared to pure PPC-P. The reason may be that the toughening agent PEO forms microcrystals in PPC-P, improving the gas barrier properties of the material.
[0115] Compared with the existing commercial PBAT films, PBS films, and traditional LDPE films, PET films, the composite films after the modification of PPCX and PPC-P have greater comprehensive performance advantages and are expected to replace traditional plastic films.
[0116] (3) The antibacterial performance of Examples 1-8 and Comparative Examples 1-5 was tested. The test method refers to "GB / T 31402-2023 Determination of Antibacterial Activity on the Surface of Plastics and Other Non-porous Materials". The test strains of Staphylococcus aureus, Escherichia coli, and Candida albicans were used. Nutrient agar was used to culture bacterial culture dishes. A sterile inoculation loop was used to inoculate 4 loops in a zigzag pattern. After culturing at 37°C for 48 h, the results were observed. The antibacterial effect of the sample in Example 1 is as shown in the appendix Figure 3 As shown. It can be known from the experimental tests that the surfaces of the experimental samples have relatively good antibacterial effects against Staphylococcus aureus, Escherichia coli, and Candida albicans, and no bacterial reproduction appears on the film surface, indicating that the plastic film prepared by the technology of the present invention has a broad-spectrum antibacterial effect.
[0117] In addition, the present invention also tested the antibacterial performance of the samples developed in Examples 2-8. The antibacterial effects are equivalent to those in Example 1, and have relatively good antibacterial effects against Staphylococcus aureus, Escherichia coli, and Candida albicans, and no bacterial reproduction appears on the film surface.
[0118] The above are only the preferred embodiments of the present invention. It should be pointed out that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. A completely biodegradable resin, characterized in that, It includes the following raw materials: Carbon dioxide-based polycarbonate, toughening agent, anti-blocking agent, additives; The carbon dioxide-based polycarbonate includes any one or a mixture of two or more of PPC-P, PPCX, and PPC-Plus biodegradable polyester resins.
2. The completely biodegradable resin according to claim 1, wherein, The toughening agent includes any one or a mixture of two or more of polyethylene oxide, polypropylene oxide, polycarbonate-co-polyurethane copolymer, poly(methyl ethylene carbonate), and aliphatic polycarbonate diol.
3. The completely biodegradable resin according to claim 1, characterized in that, The anti-blocking agent includes any one or a mixture of two or more of paraffin, stearic acid soap, fatty acid amide, polydimethylsiloxane, and talcum powder.
4. The completely biodegradable resin according to claim 1, wherein The additives include fatty acids and their salts.
5. The preparation method of the fully biodegradable resin according to any one of claims 1-4, characterized in that, It includes mixing the raw materials evenly according to the proportion, drying, melt blending and extruding with a screw, cooling, and pelletizing to obtain the modified completely biodegradable resin.
6. The preparation method of the completely biodegradable resin according to claim 5, characterized in that, The temperature of the drying is 50°C to 70°C, and the drying time is 8 to 10 h.
7. The preparation method of the completely biodegradable resin according to claim 5, characterized in that, The temperature range of the screw melt blending is 120°C to 170°C.
8. Application of a completely biodegradable resin, characterized in that, Using the completely biodegradable resin as the raw material to prepare a plastic film, and the thickness of the plastic film is 5 μm to 200 μm.
9. The application of the fully biodegradable resin according to claim 8, characterized in that, Coating the antibacterial liquid on both sides of the plastic film, and the composition of the antibacterial liquid includes 0.5% to 5% of antibacterial agent, 0.5% to 2% of silane coupling agent, and 93% to 99% of absolute ethanol.
10. The application of the fully biodegradable resin according to claim 9, wherein, The silane coupling agent includes any one of KH-550, KH-560, KH-570, A151, and A171.
Citation Information
Patent Citations
Ternary copolymerized quaternary ammonium salt macromolecular antibacterial agent as well as preparation method and application thereof
CN117304390A
Polyolefin elastomer (POE) toughened polycarbonate composite material and preparation method thereof
CN103554869A
Ternary carbon dioxide-based copolymer degradable flexible film material and preparation method thereof
CN117209989A
Biodegradable shape memory high-barrier transparent composite material, preparation method and application
CN119798953A